If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 2x + -1x = 2(100 + 3x) Combine like terms: 9x + 2x = 11x 11x + -1x = 2(100 + 3x) Combine like terms: 11x + -1x = 10x 10x = 2(100 + 3x) 10x = (100 * 2 + 3x * 2) 10x = (200 + 6x) Solving 10x = 200 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 10x + -6x = 200 + 6x + -6x Combine like terms: 10x + -6x = 4x 4x = 200 + 6x + -6x Combine like terms: 6x + -6x = 0 4x = 200 + 0 4x = 200 Divide each side by '4'. x = 50 Simplifying x = 50
| 128=16t^2+96t | | 2(7+28)= | | 16x+44y=20 | | (18-3i)(-7+8i)=0 | | 24=4x-1 | | 2(7+w)+2(w)=126 | | -5x-2.8=9x+0.4 | | -9i(4+12i)=0 | | 2(7+w)+2(w)= | | -3(4n-8)=-36 | | t^2+6t+40=0 | | 15x^-2y^4/-3^2x^-5y^8 | | 30=.75x | | 4/25=100 | | 2.8x-0.9=5.2x-33 | | t^2+12t+40=0 | | x^2-10x+31=0 | | (16+9i)-(12+9i)=0 | | 6x+2(2+7)=46 | | (x-2)*(x-3)*(x-4)*(x-5)=0 | | 3-(5x-23)=7(x-3) | | log(5)(5x+9)=log(5)(6x) | | -3(n-3)-(-5n-2)=n | | 6x+3(x-10)=61-(x-1) | | (x-2)*(x-3)*(x-4)*(x-5)=360 | | 7/9(0.8) | | 16+19+x=56 | | 4x5/12 | | (14+10i)+(-4-18i)=0 | | 287=7(1-6n) | | 5x-5=85 | | 1-9(4d-2)-6d= |